Age, Sex and Seasonal Variations of Dermatosis Attending in Dermatology Department of A Tertiary Care Hospital - Mannan, Shamsun Nahar Binte; Alam, Md Zahangir; Biswas, Rajat Sanker Roy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Dermatological problems are common among patients of different ages visiting the out patient departments of tertiary care centers. So the objective of the study to see the spectrum of pediatric and adult dermatoses in out patient skin department of Chattagram Maa hishu O General Hospital. Methods: The medical records of children and adult attending the dermatology outpatient clinics of Chattagram Maa-O-Shishu Hospital for the year September 2015 to September 2016 were retrieved. Data of 8534 patients were included. Demographic data (Age and sex) and diagnoses were collected and analyzed. Results: Among 8534 patients attended in OPD, majority of the patients were female and children (2500, 56% &, 3622, 42%). Infection constituted most of the dermatosis (31%) of which scabies was found most common (46%), eczema comes after (20%) and contact dermatitis prevailed (18%). Regarding seasonal variations majority of the patient peaked in summer 855 (10%). Among all 14 patients of epidermolysis bullosa were found. Leprosy and skin tuberculosis were found. Rare diseases including epidermal nevus syndrome 1case, tuboeruptive xanthoma in children, 2 cases, subcutaneous fat necrosis in neonate -2 cases, atypical presentation of erythema multiforme were found. Conclusion: Many children and almost all adult presents with uncommon presentation of common disease due to frequently visiting non professional and traditional medicine practitioners and homeopathic and traditional medicine. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 47-49